The overlap between miscarriage and extreme preterm birth in a limited-resource setting on the Thailand-Myanmar border: a population cohort study - McGready, R; Paw, MK; Wiladphaingern, J; Min, AM; Carrara, V; Moore, K; Pukrittayakamee, S; Nosten, F (F1000Research, 2016)
Background: No universal demarcation of gestational age distinguishes miscarriage and stillbirth or extreme preterm birth (exPTB). This study provides a synopsis of outcome between 22 to <28 weeks gestation from a low resource setting. Methods: A retrospective record review of a population on the Thailand-Myanmar border was conducted. Outcomes were classified as miscarriage, late expulsion of products between 22 to < 28 weeks gestation with evidence of non-viability (mostly ultrasound absent fetal heart beat) prior to 22 weeks; or exPTB (stillbirth/live born) between 22 to < 28 weeks gestation when the fetus was viable at ≥22 weeks. Termination of pregnancy and gestational trophoblastic disease were excluded. Results: From 1995-2015, 80.9% (50,046/ 61,829) of registered women had a known pregnancy outcome, of whom 99.8% (49,931) had a known gestational age. Delivery between 22 to <28 weeks gestation included 0.9% (472/49,931) of pregnancies after removing 18 cases (3.8%) who met an exclusion criteria. Most pregnancies had an ultrasound: 72.5% (n=329/454); 43.6% (n=197) were classified as miscarriage and 56.4% (n=257) exPTB. Individual record review of miscarriages estimated that fetal death had occurred at a median of 16 weeks, despite late expulsion between 22 to <28 weeks. With available data (n=252, 5 missing) the proportion of stillbirth was 47.6% (n=120), congenital abnormality 10.5% (24/228, 29 missing) and neonatal death was 98.5% (128/131, 1 missing). Introduction of ultrasound was associated with a 2-times higher odds of classification of outcome as exPTB rather than miscarriage. Conclusion: In this low resource setting few (<1%) pregnancy outcomes occurred in the 22 to <28 weeks gestational window; four in ten were miscarriage (late expulsion) and neonatal mortality approached 100%. In the scale-up to preventable newborns deaths (at least initially) greater benefits will be obtained by focusing on the viable newborns of ≥ 28 weeks gestation.